Study of the Benefits of Mangrove Conservation on Hydrometeorological Disaster Mitigation Effort in the Coastal Area, Banda Aceh City - Wien Mulia Utama; M. Farhan Selian; Alde Fitrianda (Budapest International Research and Critics University, 2022)
The city of Banda Aceh, which is a city affected by the Hydrometeorological Disaster in 2004, still has a high level of sea waves and coastal abrasion. Still, conservation of mangrove plants as a mitigation measure has not been carried out optimally due to a lack of public awareness and priority of the government's performance program plan. This study will describe a study related to the benefits of mangrove plants as an appropriate mitigation effort according to the geographical conditions of Banda Aceh City. Based on this research, it is hoped that the government and the community will understand the importance of preserving and conserving mangroves to improve the safety and security of the people in the city's coastal areas. This study uses qualitative methods based on primary and secondary data from previous journal research and data from agencies related to hydrometeorological disaster management. The results obtained are based on the data collected. Considering the study of the benefits of mangroves, the coastal city of Banda Aceh is vital for the conservation of mangrove plants as a mitigation measure for high waves and coastal abrasion.